Pengaruh Media Sosial Terhadap Karakter Anak - Malelak, Difly (Indo Green Journal, 2024)
Social media is a medium that attracts various groups to adapt to anyone openly, comment, and share various information in a very fast time without any specific time limit. The research method used is a descriptive qualitative method that uses the literature study method which aims to gain an in-depth understanding of certain phenomena by analyzing various relevant literature sources. The purpose of this research is to find out what social media is, what are the positive and negative impacts of social media on children and ethics in social media. The results of this discussion are, children are very young influenced by social media where if children are given the freedom to use social media, children will be influenced and potentially damage children's character.